Comparative study of the short-range structure of α-V2O5, α-TeO2 and xV2O5-(100 - x)TeO2 glasses using X-ray diffraction, Rietveld analysis and reverse Monte Carlo simulations - Kaur, Navjot; Khanna, Atul; Kaur, Puneet; Singh, M. N.; Sinha, A. K.; Neder, Reinhard (Acta Crystallographica Section B: Structural Science, Crystal Engineering and Materials, 2023)
Vanadium-tellurite glasses, tetragonal TeO2 and orthorhombic V2O5 crystalline samples were characterized for their atomic structure properties by synchrotron X-ray diffraction, pair distribution function analysis, reverse Monte Carlo simulations (RMC) and Rietveld analysis. The pair correlation function, G(r), of V2O5 shows the first peak at 1.61 Å. G(r) of TeO2 shows three peaks at 1.57, 2.13 and 2.88 Å due to Te-O linkages of three different lengths, whereas the Te-Te atomic pair correlation shows a peak at 3.85 Å. The average coordination number of V with O in crystalline V2O5 is 4.39 while that of Te with O in crystalline TeO2 is 3.71. G(r) of the vanadium tellurite glass shows the first peak at 1.90 Å due to overlapping Te-O and V-O atomic pair correlations. The RMC analysis on diffraction data of glasses found that the V-O coordination number is in the range 5.27-5.59 and the Te-O coordination number is 5.39-5.67. However, it is found that these coordination numbers cannot be clearly defined due to short-range disorder.
CRIS-Team Scopus Importer:2023-03-17
Keywords: reverse Monte Carlo simulations; Rietveld analysis; V2O5 and TeO2; vanadium tellurite glasses; X-ray diffraction and structure